Research on the Development Path of “Dual-Teacher Model” Educators: Industry Practice Dilemmas and Breakthroughs for Cruise Catering Service Teachers - Zhang, Xiaowei; Jiang, Rui (Journal of Research in Vocational Education, 2025)
The cultivation of “dual-teacher model” (shuāngshī xíng) educators in the field of cruise catering services is a crucial link in enhancing the adaptability of vocational education. However, this workforce currently faces prominent challenges such as low participation in corporate practice and lagging updates to industry knowledge. Grounded in Communities of Practice theory and the TPACK framework, this study, through semi-structured interviews and empirical investigations at maritime colleges, uncovers a triple dilemma in teachers’ corporate practice: high entry barriers for internships at cruise companies lead to scarce practice opportunities; the rapid international iteration of service standards widens the knowledge gap; and the misalignment between school and enterprise evaluation systems inhibits collaborative motivation. Further analysis reveals that Germany’s “dual system” teacher training model and the corporate practice policies of Australian TAFE colleges offer transferable insights. Based on this, the study proposes a three-dimensional breakthrough path: constructing a stepped corporate practice system encompassing “basic skills - emergency management - cultural innovation”; developing a dynamic knowledge update platform featuring VR-simulated service scenarios; and establishing a mutually empowering collaboration mechanism based on “converting teachers’ corporate practice outcomes into credits and mutual recognition of enterprise mentors’ professional titles”.